Problemas ambientales y sus efectos en el desarrollo turístico en la Parroquia El Guayacán, ciudad de Quevedo, año 2019 - Intriago López, Cristhian Fernando (2020)
In the environment there are factors that are harmful for life and especially for human health, such as chemical, biological, social and psychosocial factors, which in turn if they continue to potentiate will continue to affect the present and future generations' health. On a larger scale, such as pollution, water quality, waste management, not knowing how to recycle them to avoid further contamination, are what constantly endangers the health of citizens in general. Environmental problems have had negative effects on Ecuador's tourism development such as destruction of the animals' habitat, alterations in the ecosystem, due to the mismanagement of toxic waste, garbage waste, water floor pollution, deforestation, indiscriminate use of pesticides becoming a critical problem enemies of the environment directly affecting its inhabitants, economic sector, which causes the destruction of ecosystems and the degradation of natural resources, which are part of the tourist attractions that Ecuador has, these problems Environmental factors are a reality that every day become more complex and difficult to control if the necessary measures are not taken to safeguard environmental quality